Foreign language speaking anxiety of Jordanian freshman English learners - Jafar Mohammad Batiha,; Rosniah Mustaffa,; Noorizah Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Mastering English language skills is significant, particularly with respect to speaking for Jordanian undergraduates because the English language is becoming vital in some sectors in Jordan like tourism, foreign affairs, and higher education. Generally, it has been acknowledged that foreign language (FL) speaking anxiety hinders the attempts of language learners to become involved in speaking activities. Nevertheless, some studies have been conducted to probe language anxiety in general and anxiety pertaining to other language skills in Jordan. However, none of these studies was designed intentionally to address the specific FL speaking anxiety. Thus, the current research was meant to address the factors contributing to English FL speaking anxiety in the Jordanian context. To do so, in-depth, one-to-one semi-structured interviews were conducted with twenty freshman students attending Jadara University in Irbid, Jordan. NVivo software was used to manage the coding procedure in analysing the data, and respondents declared twelve factors leading to an increased level of speaking anxiety. All were like the findings of previous empirical studies except four new sources: fear of being perceived as showing-off, cultural barrier between male and female students, fear of impromptu questions and previous experience in school. The first two of these factors highlight the importance of considering the cultural backgrounds of learners when teaching English in an Arabic and/or Muslim context like Jordan. The other two factors reveal the inadequacy of English as a Foreign Language (EFL) teaching in schools, and universities too. The results support the theory that cultural differences are significant in addressing the issue of Foreign Language Speaking Anxiety (FLSA). Identification of these factors could lead future research, language teachers, and educators in better understanding of English language learning in the context of Jordan and move forward to develop strategies and tactics to overcome the difficulties triggered by speaking anxiety.